TATANAN MASYARAKAT PADA JL. PINTU AIR SITI RJO I, KEC. MEDAN KOTA, KOTA MEDAN, SUMATERA UTARA - Cut Putroe Rahma Balqis; Rika Amelia; Evy Mutiara; Putri Fadhillah Ramadhani; Mustofa Kamal; Nurjannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the social order on Jl. Pintu Air Sisingamangaraja, Medan Kota District, by examining the social structure, interaction patterns, economic activities, and dynamics of community life formed in this densely populated urban environment. Using a qualitative approach through field observations, interviews with community leaders and local residents, and documentation reviews, this study attempts to provide a comprehensive picture of the developing social relations, the level of cohesion among residents, and the influence of the physical conditions of the environment on community social behavior. The research findings indicate that the social order in this area is formed through a combination of cultural factors, the informal economy, and the proximity of settlements that encourage intensive social interaction, but also give rise to several challenges such as spatial irregularities, economic competition, and diversity of social backgrounds. Nevertheless, the community is still able to build forms of social adaptation through kinship networks, neighborhood cooperation, and mutual cooperation practices that serve to maintain social stability amidst the ongoing changes and developments in urban areas.